We Are Not Slaves : State Violence, Coerced Labor, and Prisoners' Rights in Postwar America - Chase, Robert T. (Book collections on Project MUSE., 2020)
"In the early twentieth century, the brutality of southern prisons became a national scandal. Prisoners toiled in grueling, violent conditions while housed in crude dormitories on what were effectively slave plantations. This system persisted until the 1940s when, led by Texas, southern states adopted northern prison design reforms. However, the transition to penitentiary cells only made the endemic violence more secretive, and the reformers' efforts had only made things worse--now it was up to the prisoners to fight for change. Drawing from three decades of legal documents compiled by prisoners, Robert T. Chase narrates the struggle to change prison from within. Told from the vantage point of the prisoners themselves, this book highlights untold but devastatingly important truths about the histories of labor, civil rights, and politics in the United States"--Publisher's description